Pengembangan Pengembangan dan Uji Sederhana Variasi Latihan Kelenturan Berbasis Permainan pada Mahasiswa PJKR C Stambuk 2023 - Ade Ros Riza; Ariel Ginting; Titus manik; Firyal salsabila; Nurul Ikhwani; Dimmichael Ginting; Muhammad Arif Fadly (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to develop and test the effectiveness of game-based flexibility training variations for class C Physical Education, Health, and Recreation (PJKR) students, class C, class of 2023. This study was motivated by the low interest of students in participating in flexibility training which tends to be monotonous, so that more interesting and interactive learning innovations are needed. The method used is research and development (R&D) with the Borg and Gall model which has been modified into four stages, namely: needs analysis, product design, limited trials, and evaluation. The research subjects were 20 students. Data collection was carried out through observation, student response questionnaires, expert validation, and flexibility tests using the sit and reach test. Data analysis was carried out descriptively quantitatively and statistical tests using paired sample t-tests to determine differences before and after treatment. The results showed that the developed product obtained the category of "very feasible" based on the assessment of material experts and "very interesting" based on student responses. In addition, the results of statistical tests showed a significant increase in students' flexibility abilities after treatment (p < 0.05). Thus, the developed training model is declared effective, interesting, and can be used as an alternative in physical fitness learning.